Eksistensi Bahasa Jawa Bagi Masyarakat Jawa Di Era Westernisasi Bahasa - Yemima Ayu Putri Josaphat; Annisa Nur Cahyaningrum; Hafizrul Ladifa; Sabrina Fahma Nakhya Syach; Serena Wina Coren Khana (Fakultas Ilmu Budaya, Universitas Jambi, 2022)
Westernization is a typical of western culture in terms of behavior, dress, culture, language, and so on. It can be concluded that westernization is a process for one to overdo western culture without choosing and filtering it first. In the study we raised the problem of what westernization is, what language westernization is, what are the factors that cause the loss of Javanese in Java, the impact that can become of the language westernization in Java and the solutions that can be made to the problem. The purpose of the study is to know the meaning of westernization and the Javanese existence for the Javanese people, to know the effects of the language westernization in Javanese and seek solutions to preserve the existence of javan. In doing this we used qualitative research methods using observation and interview techniques, observation that is by data collection techniques done through an observation, along with note-keeping of the circumstances or behavior of the target. While interviews are done with data collection through a one-way verbal and oral questioning process, that means questions come from the one who interviews and answers are given by the one in the interview. The result of the interview is that almost all of the youth know about the meaning of the term westernization they already do. But even though they were born and raised in Java, most of them didn't understand small but rough Javanese that they used to talk to their peers. Keywords: Westernization, language culture, Javanese Languange, existence